2015
DOI: 10.1016/j.gaitpost.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Attuning one's steps to visual targets reduces comfortable walking speed in both young and older adults

Abstract: Comfortable walking speed (CWS) is indicative of clinically relevant factors in the elderly, such as fall risk and mortality. Standard CWS tests involve walking on a straight, unobstructed surface, while in reality surfaces are uneven and cluttered and so walkers rely on visually guided adaptations to avoid trips or slips. Hence, the predictive value of CWS may be expected to increase when assessed for walking in more realistic (visually guided) conditions. We examined CWS in young (n=18) and older (n=18) adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
4
10
0
1
Order By: Relevance
“…A cause of the difficulty was perhaps that only two incoming steps were seen in advance by the subject, which could be too short a warning to anticipate precise foot placement. Peper et al 30 , using the same treadmill as in the present study, showed that individuals spontaneously chose a lower walking speed in VC condition: this corroborates the hypothesis that a sufficient reaction time to the incoming targets should be allowed to help the subject to be comfortable with VC. However, further studies are needed to analyze gait variability at different speeds under VC condition.…”
Section: Author's Accepted Versionsupporting
confidence: 88%
“…A cause of the difficulty was perhaps that only two incoming steps were seen in advance by the subject, which could be too short a warning to anticipate precise foot placement. Peper et al 30 , using the same treadmill as in the present study, showed that individuals spontaneously chose a lower walking speed in VC condition: this corroborates the hypothesis that a sufficient reaction time to the incoming targets should be allowed to help the subject to be comfortable with VC. However, further studies are needed to analyze gait variability at different speeds under VC condition.…”
Section: Author's Accepted Versionsupporting
confidence: 88%
“…Table 1) for other tasks. Recent studies reported slower self-selected walking speeds in visuolocomotor situations (e.g., walking on a narrow path [26] or a sequence of stepping stones [27]) compared to unconstrained walking, for young and older adults alike. This was interpreted as an adaptive strategy to favor task performance relative to the visual context [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported slower self-selected walking speeds in visuolocomotor situations (e.g., walking on a narrow path [26] or a sequence of stepping stones [27]) compared to unconstrained walking, for young and older adults alike. This was interpreted as an adaptive strategy to favor task performance relative to the visual context [26,27]. Given our current results, it thus seems likely that older adults slowed down their preferred walking speed to increase the available time for visuolocomotor control [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two challenging walking environments differed with regard to the type of context: a stationary physical context versus suddenly appearing projector-augmented visual context. The latter context was included as projector-augmented walking-adaptability treatment is increasingly used as part of rehabilitation after stroke [ 9 , 13 15 ]. We expected stronger cognitive-motor interference for the two challenging walking environments, as reflected in lower walking speeds, poorer walking-adaptability performance, and/or poorer cognitive-task performance.…”
Section: Introductionmentioning
confidence: 99%